2022
DOI: 10.1002/marc.202200119
|View full text |Cite
|
Sign up to set email alerts
|

Polymerized Naphthalimide Derivatives as Remarkable Electron‐Transport Layers for Inverted Organic Solar Cells

Abstract: Two polymerized naphthalimide derivatives, named as N-TBHOB and N-DBH, are prepared by quaternization. They exhibit excellent performance as electron-transport layers (ETLs) in inverted organic solar cells (i-OSCs). The results indicate N-TBHOB with a reticulated structure owns a superior performance on electron extraction, electron transport, thickness tolerance, and less carrier recombination compared with N-DBH with linear structure. The i-OSCs based on N-TBHOB with PTB7-Th:PC 71 BM as the active layer achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Yet, shortcomings such as poor processability and stability result in films that are inhomogeneous in composition and continuity. ,, To address these challenges, researchers have developed a range of new CILs aimed at improving the stability and PCE of Y6-based OSCs. For instance, Xie et al synthesized a series of diimide-based molecules with special functional groups that complex Zn 2+ after deprotonation . Additionally, certain organic materials have been proven to be efficient in inverted devices. These CILs must possess the ability to increase the physical contact between components while simultaneously lowering the WF of the cathode in OSCs. However, it is important to note that highly polar groups in interfacial molecules can lead to high interfacial tension between blends and interlayers, which is not beneficial for enhancing the performance of devices. , Therefore, it is crucial for high-quality CILs to have low molecular polarity and appropriate energy levels and to maintain moderate crystallization. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Yet, shortcomings such as poor processability and stability result in films that are inhomogeneous in composition and continuity. ,, To address these challenges, researchers have developed a range of new CILs aimed at improving the stability and PCE of Y6-based OSCs. For instance, Xie et al synthesized a series of diimide-based molecules with special functional groups that complex Zn 2+ after deprotonation . Additionally, certain organic materials have been proven to be efficient in inverted devices. These CILs must possess the ability to increase the physical contact between components while simultaneously lowering the WF of the cathode in OSCs. However, it is important to note that highly polar groups in interfacial molecules can lead to high interfacial tension between blends and interlayers, which is not beneficial for enhancing the performance of devices. , Therefore, it is crucial for high-quality CILs to have low molecular polarity and appropriate energy levels and to maintain moderate crystallization. ,, …”
Section: Introductionmentioning
confidence: 99%
“…24,25 On the one hand, imide units, and more specifically naphthalimide derivatives, are often used as strong electron-acceptor moieties to obtain processable organic materials with low-lying LUMO energy levels and good optical, electrochemical and electrical properties. [26][27][28][29][30] On the other hand, the covalent linkage of naphthalimide units with strong donor scaffolds such as oligothiophenes or triarylamines has shown to be a promising approach to obtain ambipolar materials. 31,32 Thus, in our research groups we have widely demonstrated that the combination of donor and acceptor units through different rigid and conjugated linkers can pave the way to functional materials with tunable and, sometimes unexpected, optical and electrochemical properties and good n-type or ambipolar characteristics in OFETs or OSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the PEDOT:PSS AIL is seriously unfavorable to the stability of devices, and PDI/NDI based thickness-insensitive CILs are rarely reported for inverted OSCs with the advantage of stability, which may originate from relatively poor solvent resistance and transparency of PDI/NDI based CILs. 28 In inverted OSCs, zinc oxide (ZnO) is a widely used CIL, and PDI/NDI derivatives, e.g. PBI materials, were also doped into ZnO as thickness-insensitive CILs.…”
Section: Introductionmentioning
confidence: 99%